A Survey on the Use of UML in the Brazilian Industry - Júnior, Ed; Farias, Kleinner; Silva, Bruno (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Although UML modeling has been used in the Brazilian industry in the last decade, little is known about the factors, perceptions of professionals and practices that end up affecting the UML use in real-world projects. This paper, therefore, reports on an exploratory survey focused on investigating how UML is used in practice in the Brazilian software industry. In total, 314 practitioners from 180 information technology companies answered an online questionnaire about the usage-affecting factors, difficulty and frequency of use, perceived benefits, and adoption-preventi ng contextual factors of UML models. Moreover, 20 practitioners participated in a semi-structured interview. The results show that the participants recognize the usefulness of the UML models, e.g., allowing an improved understanding of the integration among enterprise applications. However, 74.8% of the participants did not use UML models due to some factors such as continuous delivery practices, time constraints, lack of knowledge about modeling, company culture, and the ever-present difficulty of keeping the models updated and synchronized.